New Insights Into Blue Light Phototherapy in Experimental Trypanosoma cruzi Infection - Ivanova, Natália; Leite, Ana Luísa Junqueira; Vieira, Marcel Barbosa; Silva, Otto Henrique Cezar e; Mota, Ludmilla Walter Reis; Costa, Guilherme de Paula; Azevedo, Cristiano Schetini de; Auharek, Sarah Alves; Novaes, Romulo Dias; Pinto, Kelerson Mauro de Castro; Bianchi, Rodrigo Fernando; Talvani, André (Frontiers in Cellular and Infection Microbiology, 2021)
The search for an effective etiologic treatment to eliminate Trypanosoma cruzi, the causative agent of Chagas disease, has continued for decades and yielded controversial results. In the 1970s, nifurtimox and benznidazole were introduced for clinical assessment, but factors such as parasite resistance, high cellular toxicity, and efficacy in acute and chronic phases of the infection have been debated even today. This study proposes an innovative strategy to support the controlling of the T. cruzi using blue light phototherapy or blue light-emitting diode (LED) intervention. In in vitro assays, axenic cultures of Y and CL strains of T. cruzi were exposed to 460 nm and 40 µW/cm2 of blue light for 5 days (6 h/day), and parasite replication was evaluated daily. For in vivo experiments, C57BL6 mice were infected with the Y strain of T. cruzi and exposed to 460 nm and 7 µW/cm2 of blue light for 9 days (12 h/day). Parasite count in the blood and cardiac tissue was determined, and plasma interleukin (IL-6), tumoral necrosis factor (TNF), chemokine ligand 2 (CCL2), and IL-10 levels and the morphometry of the cardiac tissue were evaluated. Blue light induced a 50% reduction in T. cruzi (epimastigote forms) replication in vitro after 5 days of exposure. This blue light-mediated parasite control was also observed by the T. cruzi reduction in the blood (trypomastigote forms) and in the cardiac tissue (parasite DNA and amastigote nests) of infected mice. Phototherapy reduced plasma IL-6, TNF and IL-10, but not CCL2, levels in infected animals. This non-chemical therapy reduced the volume density of the heart stroma in the cardiac connective tissue but did not ameliorate the mouse myocarditis, maintaining a predominance of pericellular and perivascular mononuclear inflammatory infiltration with an increase in polymorphonuclear cells. Together, these data highlight, for the first time, the use of blue light therapy to control circulating and tissue forms of T. cruzi. Further investigation would demonstrate the application of this promising and potential complementary strategy for the treatment of Chagas disease.